The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Organic Reactions 2017
DOI: 10.1002/0471264180.or093.01
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, Rhodium‐Catalyzed 1,4‐Addition of Organoboron Reagents to Electron‐Deficient Alkenes

Abstract: The rhodium‐catalyzed 1,4‐addition of organoboron reagents to electron‐deficient alkenes is a versatile method for the enantioselective construction of carbon–carbon bonds. The scope of these reactions is broad, and alkenes activated by adjacent carbonyls, imines, nitriles, phosphonyl groups, nitro groups, sulfonyl groups, C=N‐containing aromatic heterocycles, electron‐deficient arenes, or boryl groups are effective substrates. Regarding the pronucleophilic component, aryl‐, heteroaryl‐, and alkenylboron reage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 316 publications
0
9
0
Order By: Relevance
“…However, without recourse to harsh bases, classical deprotonation strategies are largely limited to stabilized nucleophiles bearing moderate to strong electron-withdrawing groups (e.g., ketones and 1,3-dicarbonyl compounds) . Lewis acid catalysis has been employed to expand the scope of Michael addition to less acidic pronucleophiles (e.g., simple esters and nitriles), while the use of preformed organometallic reagents and stable enol equivalents has further broadened the scope of 1,4-addition chemistry to nucleophiles that would be difficult to generate selectively by in situ deprotonation. However, the need for prefunctionalization steps reduces the attractiveness and practicality of protocols that call for preformed nucleophiles, particularly if the requisite organometallic reagent is complex or functional group-rich.…”
mentioning
confidence: 99%
“…However, without recourse to harsh bases, classical deprotonation strategies are largely limited to stabilized nucleophiles bearing moderate to strong electron-withdrawing groups (e.g., ketones and 1,3-dicarbonyl compounds) . Lewis acid catalysis has been employed to expand the scope of Michael addition to less acidic pronucleophiles (e.g., simple esters and nitriles), while the use of preformed organometallic reagents and stable enol equivalents has further broadened the scope of 1,4-addition chemistry to nucleophiles that would be difficult to generate selectively by in situ deprotonation. However, the need for prefunctionalization steps reduces the attractiveness and practicality of protocols that call for preformed nucleophiles, particularly if the requisite organometallic reagent is complex or functional group-rich.…”
mentioning
confidence: 99%
“…The rich chemistries afforded by homogeneous Rh­(I) catalysis have been studied within academia for decades and more recently have attracted attention within process research and development in the fine chemical industry. For example, Rh­(I)-catalyzed hydrogenation has been a popular transformation on process scale, and other industrial applications include Rh­(I)-catalyzed hydroformylation, conjugate addition, C–H functionalization, and transfer hydrogenation …”
Section: Introductionmentioning
confidence: 99%
“…The present asymmetric reaction proceeded as well with a bisphosphine ligand, ( R )-binap, although the enantioselectivity was lower (entry 9). The reaction in dioxane/H 2 O, which is a homogeneous solvent system commonly used for rhodium-catalyzed arylation reactions, gave 3aa with slightly lower enantioselectivity (93% ee) (entry 10). At 30 °C, the reaction was slow, giving 48% yield of 3aa , together with recovery of 39% of 1a as a racemic mixture (entry 11).…”
mentioning
confidence: 99%
“…Dynamic kinetic resolution (DKR) in asymmetric synthesis has been proven to be an ideal method of preparing enantioenriched products from racemic substrates, and it consists of racemization of a chiral substrate and kinetic resolution of the racemized substrate. Recently, Johnson reported a novel DKR in the rhodium-catalyzed asymmetric arylation of achiral γ-alkyl α-angelica lactones, giving β,γ-disubstituted γ-butyrolactones with high enantio- and trans-selectivity, where the racemization of chiral α,β-unsaturated lactone takes place through its equilibration with an achiral alkenyl ester (Scheme a). Here, we report a lactam version of the same type of DKR. In addition to the high synthetic utility of the arylated lactam products, the present reaction has an advantage over the lactone version in that an appropriate choice of the substituents on the lactam nitrogen would give us a chance to attain high efficiency in the DKR by controlling the racemization rate as well as the reactivity and enantioselectivity at the rhodium-catalyzed arylation. We found that the use of Boc (COO t -Bu) as a protecting group on the lactam nitrogen together with a chiral diene ligand L1a on the rhodium catalyst enabled the DKR in the asymmetric conjugate arylation/alkenylation of γ-substituted α,β-unsaturated γ-lactams ( rac - 1 ) to proceed with high efficiency in all aspects (Scheme b).…”
mentioning
confidence: 99%